COMPARISON OF FETAL MIDDLE CEREBRAL ARTERY DOPPLER INDICES IN ANEMIC AND NON-ANEMIC PREGNANT FEMALES (The Research of Medical Science Review, 2025)
Maternal anemia remains a significant global health challenge, particularly in low- and middle-income countries like Pakistan, where its prevalence ranges from 38% to 60%. This condition has far-reaching implications for both maternal and fetal health, often leading to adverse pregnancy outcomes such as intrauterine growth restriction and perinatal mortality. Objective: This study investigates the impact of maternal anemia on fetal cerebral hemodynamics, focusing on middle cerebral artery (MCA) Doppler indices, including pulsatility index (PI), resistive index, peak systolic velocity (PSV), and end-diastolic velocity (EDV). Methods: A cross-sectional design was employed to analyse data from 120 pregnant women, categorized into anemic and non-anemic groups based on hemoglobin levels. Doppler ultrasound was used to measure MCA indices, and statistical analyses were conducted to compare these parameters between the two groups. Results: Significant alterations in MCA Doppler indices were observed in anemic pregnancies, including reductions in PI (1.15 ± 0.15 vs. 1.32 ± 0.18) and RI (0.55 ± 0.05 vs. 0.61 ± 0.06), alongside increases in PSV (69.74 ± 8.65 cm/s vs. 57.83 ± 6.46 cm/s) and EDV (31.63 ± 6.79 cm/s vs. 23.08 ± 5.85 cm/s). Conclusion: The study highlights that early detection and effective management of maternal anemia is highly important to avoid adverse effects on fetal development. Timely interventions, including routine screening and supplementation of micronutrients, have a major impact on pregnancy outcomes.